Basketbol larong Pinoy - Aguilar, Mila D.; Selvido, Ma. Ernie; Institute for Filipino Cinema ([Quezon City] Institute for Filipino Cinema, 1989)
Deals with the sociology and the psychology of basketball for the Filipino fan, as seen by movie stars, a psychologist, a sociologist, and a feminist.
VHS
Editor, Mel L. Bacani III; Host, Ma. Ernie Selvido.
Keywords: Basketball -- Philippines; Sports; Human kinetics